Digital Human Resource Management dan Kinerja Karyawan di Era Tranformasi Digital: A Systematic Literature Review - Vivi Nur Fitriani; Ruli Lailatul Fitria; Desti Tampi Prabowo; Rafika Meilia Sari (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Advances in digital technology have brought about changes in human resource management, particularly through the implementation of digital human resource management approaches. Although this concept continues to evolve, there remains a lack of research that clearly explains how Digital HRM relates to improvements in employee performance. This study aims to analyze the role and mechanisms of Digital HRM in enhancing employee performance during the era of digital transformation. This study employs a qualitative approach by reviewing and analyzing the literature, specifically using thematic analysis. The data utilized comes from 25 articles published in relevant peer-reviewed scientific journals, supplemented by books and other scholarly publications. The research indicates that Digital HRM enhances employee performance through several key mechanisms: streamlining work processes to make them faster and more efficient, making decisions based on accurate data, and improving employees’ digital competencies. Digital recruitment accelerates and simplifies the hiring process; e-learning-based training expands skills in a more flexible manner; and technology-driven performance evaluations enhance clarity and boost employee motivation. Additionally, Digital HRM strengthens communication and collaboration within the company, thereby fostering a more flexible work environment that responds quickly to change. However, in practice, there are still many challenges to be addressed, such as technological readiness, organizational culture, employees’ ability to adapt, as well as data security and privacy protection issues all of which are critical factors that must be considered when implementing digital systems. From an academic perspective, this study helps clarify how Digital HRM influences employee performance and serves as a reference for further research and a resource for companies seeking to enhance the implementation of Digital HRM more effectively.